Pengaruh Persepsi Manfaat, Persepsi Kemudahan, dan Persepsi Keamanan terhadap Minat Menggunakan Financial Technology pada Aplikasi Dana - Siti Umul Khoiriyah; Achmad Syahfrudin Zulkarnnaeni; Moh Halim (LPPM POLITEKNIK LP3I BANDUNG, 2023)
This study aims to determine the effect of perceived benefits, perceived convenience, and perceived security on interest in using financial technology through e-wallet with the DANA application in Ajung District. The population used in this study is online and physical stores that use e-wallet with the DANA application as many as 53 shops in Ajung District. The sample in this study was selected using a purposive sampling technique. Shops that were sampled were 48 online stores and physical stores. The number of questionnaires distributed in this study were 53 questionnaires with 48 questionnaire data that could be processed. The data analysis technique used multiple linear regression analysis. Based on the results of the analysis and discussion, it shows that perceived benefits, perceived convenience, and perceived security have a positive effect on interest in using e-wallet with the DANA application. In addition, the results of the study partially show that the perceived benefits, perceived convenience, and security perceptions have an effect on interest in using e-wallet with the DANA application.